DIRECTIVE ILLOCUTIONARY SPEECH ACTS IN THE BOOK OF BAHRUL ADAB(PRAGMATICS STUDY) - Ratu Anti Salimah; Rohanda; Siti Muslikah (Esteem Journal of English Education Study Programme, 2025)
This research investigates the directive illocutionary speech acts found in Kitab Bahrul Adab, aiming to reveal the underlying mechanisms of effective communication within classical texts. Employing a qualitative approach, the study yields descriptive insights into both explicit and implicit forms of directives namely commands, requests, invitations, advice, criticism, and prohibitions. A total of fifty directive illocutionary acts are identified and categorized based on their communicative functions, including commanding, advising, insinuating, and threatening. The findings illuminate the pivotal role of directive speech acts in everyday interactions, while also reflecting the embedded moral and sociocultural dimensions inherent in this classical literary work.